CHOICE OF THE METHOD OF REPRESENTATION OF THE BIBLIOGRAPHIC INFORMATION - Толстиков, Александр Николаевич; Павленко, Евгений Петрович; Толстиков, Николай Григорьевич (Eastern-European Journal of Enterprise Technologies, 2010)
Advantages and disadvantages of methods of bibliographic information presentation were analyzed. The problem of account of this information was considered and also was chosen a method for its effective decision.